Capturing lifestyle changes and emotional experiences while having a compromised immune system during the COVID‐19 pandemic: A photo‐elicitation study. Issue 5 (6th January 2022) - Sinko, Laura; Rajabi, Samira; Sinko, Alyssa; Merchant, Raina
Abstract: This study aimed to describe lifestyle and emotional changes individuals with compromised immune systems experienced during the early months of the coronavirus disease 2019 pandemic. A survey was distributed to online support organizations for those with chronic illness and a national research volunteer registry from April to June 2020. Participants were asked to document their experiences via three photo‐elicitation prompts, followed by reflection and Likert scale questions. Forty‐seven individuals responded with 282 photos submitted. Lifestyle changes noted include shifts in wellness strategies, health management, routine, stressors, and time perception. Participants described significant distress stemming from deteriorating mental health, safety fears, isolation, health management, and longing. Wellness strategies documented included finding comfort, connection, and escape, managing uncertainty, maintaining physical health, and building resilience. These findings can increase a sense of community for immunocompromised individuals who are struggling in isolation and enhance knowledge of their day‐to‐day health needs during times of increased stress and health risk.